2020
DOI: 10.3390/ani10091706
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Visits to an Outdoor Range and Lower Areas of an Aviary System Is Related to Curiosity in Commercial Free-Range Laying Hens

Abstract: Individual hen preferences to spend time at particular locations within a free-range aviary system and relationships with temperament is relatively unknown. Hens (n = 769) from three commercial flocks were monitored with Radio Frequency Identification technology to determine time spent on the range, upper and lower aviary tiers, and nest boxes. Prior depopulation, novel arena (NA) and novel object (NO) tests assessed exploration and fearfulness. During early life; more time on the lower tier was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
0
15
2
Order By: Relevance
“…In contrast with the minimal impacts of rearing enrichments, outdoor rangers were found to be less fearful than the indoor hens across the OFT (both observer and automated measures) and ET, although not TI. Previous studies have also found lower-ranging hens to be more fearful [ 5 , 14 , 22 , 32 , 33 ], but not all tests across all studies reveal differences, with the TI duration showing a negative correlation with the range use in some studies [ 32 , 54 , 55 ] and no relationship in others [ 5 , 14 , 56 ]. Behavioural tests on the same hens do not always correlate and show the same differences, which is likely related to different specific aspects of the traits they are measuring.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast with the minimal impacts of rearing enrichments, outdoor rangers were found to be less fearful than the indoor hens across the OFT (both observer and automated measures) and ET, although not TI. Previous studies have also found lower-ranging hens to be more fearful [ 5 , 14 , 22 , 32 , 33 ], but not all tests across all studies reveal differences, with the TI duration showing a negative correlation with the range use in some studies [ 32 , 54 , 55 ] and no relationship in others [ 5 , 14 , 56 ]. Behavioural tests on the same hens do not always correlate and show the same differences, which is likely related to different specific aspects of the traits they are measuring.…”
Section: Discussionmentioning
confidence: 89%
“…The exposure to the range itself may then improve the adaptability of the birds or habituate them to new stimuli and, thus, decrease their fear with the increasing range use. Range use itself increases over time [ 22 , 53 ], and thus, while there may be some effects of underlying behavioural traits on the initial range access (Campbell et al, unpublished data), these traits may be modified by experiences across the lay cycle. However, the direction of the relationship between fearfulness and range use is not clear from this study, and further research applying fearfulness tests both prior to and following range usage may confirm the causality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hens given a Multi-choice environment at week 5 made the most visits, as birds from all four pens were seen outside, suggesting higher optimism or seeking. It has been suggested that more curious hens would be more likely to use an outdoor range (Kolakshyapati et al 2020). Usage of an outdoor range is important from a production perspective, since the positive welfare impact of the range, such as reduced risk of feather pecking outbreaks, depends on hens using the range (Nicol et al 2003).…”
Section: Higher Usage Of the Layer Environmentmentioning
confidence: 99%
“…It is believed that selection of modern commercial strains for production traits lead to associated changes in birds’ fearfulness and ability to cope in novel environments, affecting how they utilize outdoor areas ( Rodenburg et al, 2008 ; Campbell et al, 2016 ; Kolakshyapati et al, 2020 ). Outdoor environments expose birds to potentially stressful situations including weather (rain, wind, temperature extremes), parasites, disease, and predation ( Lay Jr et al, 2011 ; Sossidou et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%